IMPROVING THE PROFESSIONAL-METHODICAL TRAINING OF TEACHERS THROUGH DEVELOPING PEDAGOGICAL ERUDITION (Universal International Scientific Journal, 2026)
This article provides a scientific and theoretical analysis of the content of the concept of pedagogical erudition, its role in the professional activities of teachers, and the issues of improving the professional and methodological training of teachers through the development of pedagogical erudition. It also highlights the structural components of pedagogical erudition, factors for its development, and its impact on the effectiveness of the educational process.
Keywords: Pedagogical erudition, pedagogical competence, professional and methodological training, pedagogical skills, innovative pedagogy, educational effectiveness